ANALYSIS OF CONTROL BEHAVIOUR OF ARCH ON THROUGH ARCH BRIDGE CONSTRUCTION - Krisna Putra Wijaya; Thanh Trung Dang; Cokorda Agung Yujana; I Putu Deny Surastika Aditama; I Gede Dhana Putra Sanjaya (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2024)
Bridges are structures that need to be well-planned to function optimally. Bridges come in various shapes and sizes, one of them is an arch bridge. Through this thesis preparation the author tried to plan the upper structure of a bridge with an arch type on Tukad Ayung Bridge. The initial planning data includes a length of the existing bridge of 64 m and a width of 15 m. The planning method using LRFD and SAP2000 for the software. The arch rib dimensions in the planning of the through arch steel bridge on Tukad Ayung is 900.600.30.40 box profile with a cross-sectional height. It is using steel material of special type of structural steel for bridges with ASTM A 709 grade 50 specifications. From the analysis result, the stress melting point is fy= 345 MPa and the modulus of elasticity steel is E= 200000 MPa. The cross-sectional height is 900 mm, cross-sectional width is 600 mm, the body thickness (tw) is 30 mm and the wing thickness (tf) is 40 mm.